Fruit juice production using ultraviolet pasteurization: a review - Abdul Karim Shah, Nor Nadiah; Shamsudin, Rosnah; Abdul Rahman, Russly; Mohd Adzahan, Noranizan (M D P I AG, 2016)
Ultraviolet (UV-C at 253.7 nm) technology has been the go-to alternative pasteurization and shelf-life extension treatment for beverages for the last two decades. It has been the focal point of non-thermal methods for fruit juice processing and has been studied extensively. UV-C technology has been proven to produce microbiologically safe products with minimal negative impact towards quality of the products. However, due to the physicochemical characteristics of fruit juice, application of UV-C does have certain limitations and thus, there is a need to further study the effects of UV-C-treatment and equipment design. Critical decisions on the type of fruit product, juice color, juice composition, and juice physical characteristics, among other variables, are imperative to produce a safe and wholesome juice. Therefore, this paper serves as a source for development of UV-C technology for pasteurization and shelf-life extension of fruit juice to successfully obtain a final product with minimal changes of its nutritional component without neglecting the microbial safety. It reviews previous literatures involving ultraviolet-treated fruit juices, ranging from popular apple and orange juice to lesser-known pummelo and pitaya juice. The review also covers the aspect of microbiological and chemical safety, quality, and sensory characteristics as well as hurdle technology involving UV-C as the main method and the market potential with its cost implication of UV-C technology.